2020
DOI: 10.1186/s12902-020-0542-5
|View full text |Cite
|
Sign up to set email alerts
|

Dulaglutide improves glucocorticoid-induced hyperglycemia in inpatient care and reduces dose and injection frequency of insulin

Abstract: Background: Glucocorticoid (GC)-induced hyperglycemia is characterized by elevated postprandial blood glucose, which commonly requires multiple insulin injections. We investigated whether a long-acting glucagon-like peptide-1 receptor agonist, dulaglutide (Dula), safely improved GC-induced hyperglycemia in inpatients, to reduce insulin injection frequency. Methods: The data of hospitalized patients with GC-induced hyperglycemia treated with Dula (Dula group, n = 38) or without (non-Dula group, n = 38) were ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…In a study involving healthy subjects and a meal challenge test, exenatide was shown to prevent glucose intolerance and islet cell dysfunction caused by high-dose glucocorticoids [102]. Furthermore, a retrospective study of patients with GIH demonstrated that adding dulaglutide to insulin therapy resulted in glycemic control with a reduced insulin dose and frequency, while maintained safety with respect to gastrointestinal symptoms and hypoglycemia [103]. Despite these findings, there is still a need for more longterm research to conclusively determine the efficacy and safety of GLP-1RAs in the management of GIH.…”
Section: Incretin-based Agentsmentioning
confidence: 99%
“…In a study involving healthy subjects and a meal challenge test, exenatide was shown to prevent glucose intolerance and islet cell dysfunction caused by high-dose glucocorticoids [102]. Furthermore, a retrospective study of patients with GIH demonstrated that adding dulaglutide to insulin therapy resulted in glycemic control with a reduced insulin dose and frequency, while maintained safety with respect to gastrointestinal symptoms and hypoglycemia [103]. Despite these findings, there is still a need for more longterm research to conclusively determine the efficacy and safety of GLP-1RAs in the management of GIH.…”
Section: Incretin-based Agentsmentioning
confidence: 99%
“…GIH (glucocorticoid-induced hyperglycemia) is the increase in blood glycemia resulting from the short and long-term use of glucocorticoids (GCs), including methylprednisolone pulse therapy, in diabetic or non-diabetic patients. The diagnosis of GIH occurs equally with other types of diabetes, using the criteria established by the American Diabetes Association (ADA), which are: fasting blood glucose ≥ 126 mg/dL, after 2 hours another fasting blood glucose measurement or the Oral Test Glucose Intolerance (OTGI) with levels ≥ 200 mg/dL (11.1 mmol/l), glycated hemoglobin (Hb1Ac) ≥ 6.5% or random blood glucose ≥ 200 mg/dL (11.1 mmol/l) with the patient presenting signs and symptoms of hyperglycemia or hyperglycemic crisis (Aberer et al, 2021;Hwang et al, 2014;Litty et al, 2017;Nakamura et al, 2020;Uchinuma et al, 2020).…”
Section: Diagnosis and Screening Goalsmentioning
confidence: 99%
“…Recent trials have challenged the insulin-only strategy in hospitalized patients and have investigated the use of Glucagon-like peptide 1-analogues (GLP-1 analogues). [39][40][41] In GC-induced hyperglycemia, data is scarce, however a trial in healthy volunteers 42 and a retrospective observational study 43 show promising results. Not only due to the effect of GLP-1 analogues on insulin resistance and glucose tolerance, but mainly due to the low risk of hypoglycemia.…”
Section: Limitations and Strengthsmentioning
confidence: 99%